The speculative route : futures from South and Southwest Asia and North Africa - Tabur, Merve; Tabur, Merve; Khan, Sami Ahmad, 1985-; Khan, Sami Ahmad, 1985- (Studies in global genre fiction, 2026)
"The Speculative Route explores speculative traditions and science fictional modes across South and Southwest Asia and North Africa (SSWANA), examining their historical connections, inter and intra-regional entanglements, overlaps, and differences. Conceptualizing science fiction and fantasy (SFF) as a mode rather than genre, this volume challenges the putative boundaries between literary and genre fiction through critical studies and essays focusing on SFF from Bangladesh, Egypt, India, Iran, Pakistan, Palestine, Sri Lanka, and Turkey. It demonstrates the ways in which science fictional modes of thinking and imagination function as critical tools for addressing social, cultural, and political issues beyond genre conventions and expectations. Bringing together articles by leading scholars of SFF and think-pieces by acclaimed authors of contemporary SF, this volume focuses on central themes such as the relationship between aesthetics and politics, alterity, worldbuilding, memory, trauma, colonialism and decolonization, ecology, gender, religion, and mythopoetics. It engages with the past, present, and future of speculative traditions in SSWANA, and compares the visions that emerge from these seemingly disparate--but historically connected--entities. Part of the Studies in Global Genre Fiction series, this volume will be of great interest to academics, students, and practitioners in the fields of genre studies (notably, SF, SFF), comparative literature, media and popular culture, area studies, postcolonial studies, and future studies, as well as to readers who are interested in exploring SFF works from the Global South"-- Provided by publisher.